Efficacy and Safety of Direct-Acting Antivirals in Kidney Transplantation From HCV-Viremic Donors to Negative Recipients: A Meta-Analysis - Feng, Zepei; Zhang, Jinwei; Tan, Weilong; Wang, Chunhui; Chen, Qiong; Shen, Chao; Fan, Haozhi; Zhang, Yun; Huang, Peng; Yue, Ming (Frontiers in Medicine, 2022)
Background: With the development of direct-acting antiviral agents (DAAs), the research on kidney transplantation from Hepatitis C virus (HCV)-viremic donors to HCV-negative recipients has grown. The objective of this comprehensive analysis was to evaluate the efficacy and safety of DAAs in kidney transplantation from HCV-viremic donors to negative recipients. Methods Multiple databases were searched for a systematic and comprehensive up to March 2022. The primary outcomes included the percentage of sustained virological response at week 12 after the end of treatment (SVR12), adverse events (AEs; any grade), and severe adverse events (SAEs) as the endpoints. Publication bias was examined by using the funnel plots and Egger's test. Results In total, 16 studies with 454 subjects were included in the study and the pooled estimate of SVR12, AEs, and SAEs rates were 100.0% (95% CI: 99.2-100.0), 1.9%(95%CI: 0.0-4.9), and 0.0% (95%CI: 0.0-1.5). Subgroup analysis showed that pooled SVR12 rates were 100.0% (95%CI: 99.6-100.0) for genotype (GT)1a and 96.3% (95%CI: 83.3-100.0) for GT2; 100.0% (95%CI: 98.9-100.0) for DAAs treatments; and 100.0% (95%CI: 98.2-100.0) for prophylaxis subgroup. Egger's tests showed that no publication bias was found in this study. Conclusion This comprehensive analysis showed the high efficacy and safety of DAAs in kidney transplantation from HCV-viremic donors to HCV-negative recipients. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=246541.